2018
DOI: 10.1534/g3.118.200231
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Self-Incompatibility Signaling in TransgenicArabidopsis thalianaIs Independent of AP2-Based Clathrin-Mediated Endocytosis

Abstract: Internalization of plasma membrane (PM)-localized ligand-activated receptor kinases and their trafficking to sorting endosomes have traditionally been viewed as functioning primarily in the down-regulation of receptor signaling, but are now considered to be also essential for signaling by some receptors. A major mechanism for internalization of PM proteins is clathrin-mediated endocytosis (CME). CME is mediated by the Adaptor Protein Complex 2 (AP2), which is involved in interaction of the AP2 μ-adaptin subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The S-RLK proteins determine self-incompatibility responses in self-incompatible plants. In self-compatible plants, S-RLK expression is suppressed in the anthers, which might be a pre-requisite for self-pollination, because the overexpression of S-RLKs in self-compatible plants often suppresses self-pollination 41 . We have also shown that high expression levels of the phasiRNA target genes negatively regulate sporogenesis and seed setting, and reproductive phasiRNAs are involved in suppressing these RLKs.…”
Section: Discussionmentioning
confidence: 99%
“…The S-RLK proteins determine self-incompatibility responses in self-incompatible plants. In self-compatible plants, S-RLK expression is suppressed in the anthers, which might be a pre-requisite for self-pollination, because the overexpression of S-RLKs in self-compatible plants often suppresses self-pollination 41 . We have also shown that high expression levels of the phasiRNA target genes negatively regulate sporogenesis and seed setting, and reproductive phasiRNAs are involved in suppressing these RLKs.…”
Section: Discussionmentioning
confidence: 99%
“…In N- and C-terminal domains located to cytoplasm of SaCLCa2, SaCLCc2, as well as of other SaCLC proteins consensus tyrosine-based motifs YXXΦ (Φ is a hydrophobic amino acid) and dileucine-based motifs DXXLL or [DE]XXXL[LI] were found ( Figure 1 , underlined). A key role of similar motifs in sorting and subcellular localization was shown for a number of membrane A. thaliana proteins [ 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…These recruit components of the transport machinery, ensuring delivery of proteins to proper membranes [ 45 , 50 , 51 ]. Involvement of tyrosine- and dileucine-based motifs in sorting and control of subcellular localization of endocytosed plant proteins, such as auxin transporter PIN1 [ 40 ], vacuolar sorting receptor VSR4 [ 41 ], brassinosteroid receptor BRI1 [ 44 ], vacuolar transporters NRAMP3 и NRAMP4 [ 42 ], and SRK kinase [ 43 ], has been demonstrated. Analyses of amino acid sequences in S. altissima CLC proteins displayed presence of similar consensus motifs in N- and C-terminal domains located to cytoplasm ( Figure 1 , underlined).…”
Section: Discussionmentioning
confidence: 99%